Enhancing radiotherapy outcomes in rectal cancer: A systematic review of targeting hypoxia-induced radioresistance - Matthew Fok; Rhianna Hill; Hayley Fowler; Rachael Clifford; Aaron Kler; Jayanma Uzzi-Daniel; Sonia Rocha; Gabrielle Grundy; Jason Parsons; Dale Vimalachandran (Clinical and Translational Radiation Oncology, 2024)
Introduction: Neoadjuvant radiotherapy is successfully used in rectal cancer to improve overall survival. However, treatment response is both unpredictable and variable. There is strong evidence to show that the phenomenon of tumour hypoxia is associated with radioresistance, however the mechanism(s) behind this are poorly understood. Consequently, there have only been a small number of studies evaluating methods targeting hypoxia-induced radioresistance. The purpose of this systematic review is to evaluate the potential effectiveness of targeting hypoxia-induced radioresistance in rectal cancer and provide recommendations for future research in this area. Methods: A comprehensive literature search was performed following the PRISMA guidelines. This study was registered on the Prospero database (CRD42023441983). Results: Eight articles met the inclusion criteria. All studies identified were in vitro or in vivo studies, there were no clinical trials. Of the 8 studies identified, 5 assessed the efficacy of drugs which directly or indirectly targeted hypoxia and three that identified potential targets. There was conflicting in vivo evidence for the use of metformin to overcome hypoxia induced radioresistance. Vorinostat, atovaquone, and evofosfamide showed promising preclinical evidence that they can overcome hypoxia-induced radioresistance. Discussion: The importance of investigating hypoxia-induced radioresistance in rectal cancer is crucial. However, to date, only a small number of preclinical studies exist evaluating this phenomenon. This systematic review highlights the importance of further research to fully understand the mechanism behind this radioresistance. There are promising targets identified in this systematic review however, substantially more pre-clinical and clinical research as a priority for future research is needed.